Исследование степени токсичности вредных веществ, выбросы которых нормируются европейскими экологическими стандартами - Поливянчук, Андрей Павлович; Щепак, Е. Ю.; Титова, Е. Ю. (НТУ "ХПИ", 2007)
The research are carried out to integral toxicity of exhaust gases of transport engines of standardized harmful materials is explored: monooxide carboneum, hydrocarbons, nitrogen oxide and particles. The degree of toxicity of each material estimated on the basis of the suggested procedure and European ecological norms EURO.
Keywords: токсичность отработавших газов; экологическая безопасность; транспортные ДВС; методика оценки токсичности; степени токсичности веществ; нормы EURO